Novel approach to adaptive statistical process control optimisation with variable sampling interval and minimum expected loss. (1st January 2012) - Bashkansky, Emil; Glizer, Valery Y.
We investigate the properties of an adaptive control chart with a variable sampling interval, intended to be the function of an observed standard score, optimising a control performance (minimum expected loss) versus a fixed sampling interval chart scheme. In order to solve this problem its transforming to an optimal control problem is proposed. The latter is then analysed by application of Pontryagin's maximum principle. The advantage of the optimal variable sampling interval in comparison with a fixed sampling interval is demonstrated.